Petrography Characteristic of Porphyritic Dacite Rock in Olele Village, Kabila Bone, and Bone Bolango - Siti Chusnul Chatimah Nurrahmah; Ahmad Zainuri; Muhammad Kasim (Journal of Earth Energy Science, Engineering, and Technology, 2022)
Porphyritic Dacite volcanic rocks are abundant in Olele Village, Kabila Bone, Bone Bolango. This research aims to determine the petrography characteristics of porphyritic dacite rock in Olele. The methods used in this research were field observation and petrography analysis to determine rock texture, mineral composition, and micro-texture plagioclase. Olele Porphyritic Dacite has a porphyritic texture composed phenocryst of plagioclase, quartz, hornblende, sanidine, opaque mineral, and secondary minerals such as sericite and clay minerals. Rock textures include glomeroporphyritic, seriate, and embayment. The micro-textures in plagioclase are fine oscillatory zoning, synneusis, glomerocryst, fine sieve, coarse sieve, resorption surface, and broken crystal. Magmatic processes that occur in the magma chamber include fractional crystallization, magma injection, magma mixing, convection, adiabatic decompression, syn-eruption decompression, and undercooling. The secondary minerals indicated alteration hydrothermal process.